2012
DOI: 10.4028/www.scientific.net/amm.204-208.3401
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Post-Fire Behavior of Steel Fiber Reinforced Ceramsite Concrete Filled Steel Tubes

Abstract: The axial compressive mechanical behavior of steel fiber reinforced ceramsite concrete filled steel tubes (noted as SFR-CCST) after exposure to fire are experimentally studied. Effect of furnace temperature, dosage of steel fiber in specimens on the post-fire mechanical performance of the specimens after exposure to fire was especially discussed. The results show that all the specimens of SFR-CCST have higher post-fire bearing capacity and better plastic deformation, and there was no obvious descending segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Zheng [29] pointed out that when the addition of polypropylene fiber was 0.25% volume fraction, the impact strength of foamed concrete increased by 300% compared to a blank control group. To reduce the bursting and peeling of concrete shield tunnel segments under fire and to improve durability, Zhang et al [30][31][32][33][34][35] investigated the fire performance of concrete shield tunnel segments with polypropylene fibers and their mixtures. Krishna et al [36] observed that the hybrid mixture of polypropylene and micro-steel fibers exhibited good impact resistance at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng [29] pointed out that when the addition of polypropylene fiber was 0.25% volume fraction, the impact strength of foamed concrete increased by 300% compared to a blank control group. To reduce the bursting and peeling of concrete shield tunnel segments under fire and to improve durability, Zhang et al [30][31][32][33][34][35] investigated the fire performance of concrete shield tunnel segments with polypropylene fibers and their mixtures. Krishna et al [36] observed that the hybrid mixture of polypropylene and micro-steel fibers exhibited good impact resistance at high temperatures.…”
Section: Introductionmentioning
confidence: 99%